2015
DOI: 10.1002/ejoc.201500600
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Isolation of Enantiomerically Enriched Cyclopenta[b]benzofurans Based on Products from Anodic Oxidation of 2,4‐Dimethylphenol

Abstract: The anodic treatment of 2,4‐dimethylphenol offers a powerful and direct method for the construction of a dehydrotetramer with four contiguous stereocentres on a multigram scale. The installation of propellanes on this scaffold using enantiomerically pure carbonyl compounds leads to a mixture of diastereomers. This mixture is easily separable using standard chromatography and gives rise to optically pure cyclopenta[b]benzofurans which are important scaffolds in a variety of natural products. The synthesis is ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…On the other hand, in 69 % of the cases the DP4 probabilities were based on both 1 H and 13 C NMR data (as recommended by the DP4 developers) ,,,,,,,,,,,,. In the remaining cases, the 13 C NMR data was strongly preferred to compute the DP4 probability (27 %), finding only 2 examples (4 %) that were built using 1 H NMR data ,…”
Section: Dp4mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in 69 % of the cases the DP4 probabilities were based on both 1 H and 13 C NMR data (as recommended by the DP4 developers) ,,,,,,,,,,,,. In the remaining cases, the 13 C NMR data was strongly preferred to compute the DP4 probability (27 %), finding only 2 examples (4 %) that were built using 1 H NMR data ,…”
Section: Dp4mentioning
confidence: 99%
“…In fact, 71 % of papers published that reported the use of DP4 have been carried out following this approach ,,. Another interesting fact is that in 28 % of the cases the predictions made by DP4 were actually validated experimentally (mainly by total synthesis of the most likely candidate),,,,,,,,,,, indicating a clear trend for the scientific community to accept stereochemical assignments based on theoretical calculations.…”
Section: Dp4mentioning
confidence: 99%
“…558,559 In addition to generating the desired biphenol product, several additional coupling motifs can also be produced. [560][561][562][563][564][565] To circumvent the lack of selectivity, Waldvogel and coworkers realized that boron-doped diamond (BDD) electrodes 22 gave almost exclusive selectivity for the ortho-coupling product (Scheme 67). 566,567 It was rationalized that the observed selectivity originated from the high chemical and electrochemical stability of the BDD electrodes in combination with the high overpotential for oxygen evolution in aqueous media and efficient formation of reactive alkoxy or hydroxyl radicals at the anode that can serve as mediators.…”
Section: Electrochemical Oxidative Cross-couplingsmentioning
confidence: 99%
“…The electron‐rich properties associated with phenolic compounds make them particularly amenable to oxidation, a feature that makes them especially attractive in natural product synthesis . Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone .…”
Section: Anodic Oxidationmentioning
confidence: 99%